Cardi‐O‐Fix duct occluder versus amplatzer duct occluder for closure of patent ductus arteriosus. Issue 6 (9th August 2013) - Celebi, Ahmet; Demir, İbrahim Halil; Saritaş, Türkay; Dedeoğlu, Reyhan; Yucel, İlker Kemal; Demir, Fadli; Erdem, Abdullah
<x xml:space="preserve">Abstract</x> Background We sought to investigate the safety, efficacy, and follow‐up results of percutaneous patent ductus arteriosus (PDA) closure using the novel Cardi‐O‐Fix duct occluder (CDO), a device similar to but less expensive than the Amplatzer duct occluder (ADO). We also aimed to compare these two devices in terms of results. Methods Between March 2005 and May 2012, 167 patients diagnosed with moderate‐to‐large PDA underwent transcatheter closure. ADO was used in 56 (33.5%) patients with a mean age of 8.1 ± 11.9 years (3.6 months–56 years), whereas CDO was used in 111 (66.5%) patients with a mean age of 12.6 ± 14.6 years (4.8 months–63 years). Results The narrowest PDA diameter, the used device diameter, procedure time, fluoroscopy time, and residual shunt rates were similar between the two groups. Procedural success rate was 100% in both groups. Although the residual shunt rate was higher in the CDO group immediately after the procedure, the difference was not statistically significant (12.6 vs. 8.9%; P = 0.3). There was no statistically significant difference between groups at discharge and during follow‐up. No deaths occurred in any of the groups, and there were no differences in complication rates during the short‐ and mid‐term follow‐up periods (CDO 7/111 vs. ADO 5/56; P = 0.5 π). Conclusion The CDO can be used for PDA closure because of its safety, effectiveness, and simplicity in use. It is available in bigger sizes and can be used in patients with large defects. According to our short‐ and mid‐term findings, the results it yields are similar to those of the ADO; thus, it may be the preferred choice owing to its low cost and large size variability. © 2013 Wiley Periodicals, Inc.